Reusable and durable electrostatic air filter based on hybrid metallized microfibers decorated with metal–organic–framework nanocrystals. (20th September 2021) - Kim, Min-Woo; Kim, Yong-Il; Park, Chanwoo; Aldalbahi, Ali; Alanazi, Hamdah S.; An, Seongpil; Yarin, Alexander L.; Yoon, Sam S.
Graphical abstract: Highlights: Metallized microfibers with metal–organic-framework nanocrystals are fabricated. The filtration efficiency exceeds 97 % for the particulate matter size range of 0.50–1.5 μm. The dye degradation effect of the metallized microfibers has been explored. This hybrid filter is washable, reusable, mechanically durable, flexible, and transparent. Abstract: As global air pollution becomes increasingly severe, various types of fibrous filters have been developed to improve air filter performance. However, fibrous filters have limitations such as high packing density that generally causes high-pressure drop and ultimately deterioration in the filtration efficiency. High-pressure particulate matter precipitators are limited in terms of scope for commercialization because they require high voltage supplies and ozone generators. In this study, we develop fibrous filters with enhanced durability and improved performance using metallized microfibers decorated with metal–organic-framework (MOF) nanocrystals. Not only does the efficiency of the developed filters remain at or above 97 % for 0.50–1.5 μm PMs but the durability also significantly increases. In addition, using the water purification ability of the MOF, we explore the dye degradation effect of the hybrid microfibers by immersing them into Rhodamine B aqueous solution. In such an experiment the Rhodamine B aqueous solution is completely purified by the presence of the hybrid microfibers under the UV irradiation.